Exploring materials creative design for everyday objects - Alesina, Inna 1969-; Lupton, Ellen (Princeton Architectural Press, 2010)
This book is an action-oriented, accessible guide to design thinking that addresses both the how and why of product design. It encourages designers to look beyond the abstraction of pure forms or the whimsy of virtual objects, and instead to make and test real objects in a studio environment.--[book cover]